2018
DOI: 10.1093/hmg/ddy211
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, fine-mapping, and conditional analyses of genetic variants associated with C-reactive protein in multiethnic populations using the Metabochip in the Population Architecture using Genomics and Epidemiology (PAGE) study

Abstract: C-reactive protein (CRP) is a circulating biomarker indicative of systemic inflammation. We aimed to evaluate genetic associations with CRP levels among non-European-ancestry populations through discovery, fine-mapping and conditional analyses. A total of 30 503 non-European-ancestry participants from 6 studies participating in the Population Architecture using Genomics and Epidemiology study had serum high-sensitivity CRP measurements and ∼200 000 single nucleotide polymorphisms (SNPs) genotyped on the Metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 96 publications
(97 reference statements)
1
18
0
Order By: Relevance
“…35 Genetic variability in APOE has been widely related to lipid metabolism 36,37 and pro-inflammatory state measured through hs-CRP. 38,39 In this sense, results provided by Wu et al 36 showed significant differences in APOE rs7412 SNP with higher LDL-c levels in CC subjects. In our research, CC subjects from APOE rs7412 SNP showed higher apoB levels but no significant differences in LDL-c levels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…35 Genetic variability in APOE has been widely related to lipid metabolism 36,37 and pro-inflammatory state measured through hs-CRP. 38,39 In this sense, results provided by Wu et al 36 showed significant differences in APOE rs7412 SNP with higher LDL-c levels in CC subjects. In our research, CC subjects from APOE rs7412 SNP showed higher apoB levels but no significant differences in LDL-c levels.…”
Section: Discussionmentioning
confidence: 92%
“…31 On the other hand, MUFA-rich diets as MedDiet show beneficial effects in ppHTG reduction. 38,39 In this sense, results provided by Wu et al 36 showed significant differences in APOE rs7412 SNP with higher LDL-c levels in CC subjects. In our study, after long-term MedDiet consumption, APOE rs439401 SNP T-allele carriers showed a higher decrease in postprandial TG and large TRLs TG as compared to those measured before the dietary intervention, which contributes to the body of evidence supporting the beneficial effects of the MedDiet in ppHTG 32,33 and inflammatory responses.…”
Section: Ofmentioning
confidence: 92%
“…Previous studies showed that AFP promoter mutations in the distal HNF1-binding region and the proximal HNF1-binding region play important roles in regulating AFP expression [12,13]. Currently, HNF1A gene variants are associated with maturity onset diabetes of the young (MODY) [14,15], Creactive protein (CRP) levels [16][17][18], gamma-glutamyl transferase (GGT) levels [19,20], total cholesterol (TC) levels [21], pancreatic cancer [22], coronary artery disease [21,23], and metabolic syndrome (MS) [24]. The most common variants in HNF1A are rs1169288 (A/C, Ile27Leu), rs2464196 (G/A, Ser487Asn), and rs1169310 (C/T), which have been reported to be associated with the CRP level, coronary artery disease, and diabetic retinopathy [17,18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…42 The complexities of PRS in the context of ancestry and the potential to exacerbate health disparities has been addressed in-depth in recent articles. 40,42 Importantly, in addition to limitations in transferability conferred by ancestry-related genomic differences, there can be substantial variation in the performance of PRS for complex genetic Lipoprotein(a) 112 Chronic obstructive pulmonary disease 113 Rh antigens 114 Population Architecture using Genomics and Epidemiology II (PAGE II) study Adiposity traits [115][116][117] Serum lipids 118 Glycemic traits 119 QT interval 120 Age of reproductive events among women 121 C-reactive protein 122 Blood pressure 123 Complex traits 107 The Blood pressure 109,126,127 Serum lipids [128][129][130] The traits based on methodological decisions 40 and on environmental context. 44 If PRS do become useful clinically, the limitations of applying data from a subset of the global population to all global populations are clear.…”
Section: Improvements In Clinical Carementioning
confidence: 99%